Relationship between job resources and job embeddedness among tertiary-level public hospital nurses: parallel mediating roles of work–family conflict and work–family enrichment - Yujie Zhang; Shanyan Lei; Fang Yang (Frontiers in Public Health)
ObjectiveThis study explored the relationship between job resources and job embeddedness among tertiary-level public hospital nurses and the mediating role of work–family conflict and work–family enrichment.MethodsData were collected from 1,420 nurses at five tertiary-level public hospitals in China. Measurements included job resources, work–family conflict, work–family enrichment, and job embeddedness. A descriptive analysis, t-test, one-way analysis of variance, hierarchical multiple regression analysis, and structural equation model were used to analyze the data.ResultsNurses’ job embeddedness was 23.57 ± 5.99. Job embeddedness for nurses varied according to age, education, employment type, years of service, work intensity, and health status (all p-values < 0.05). Nurses’ job resources were positively associated with job embeddedness (β = 0.214, p < 0.01). Nurses’ work–family conflict and work–family enrichment had a parallel mediating effect between job resources and job embeddedness, with mediating effect values of 0.120 and 0.044, respectively (p < 0.01). Regarding the specific dimensions of job resources, social supports, and skill diversity have the largest coefficients on job embeddedness (β = 0.288, β = 0.374), and both have direct and indirect association with job embeddedness.ConclusionNurses’ job resources were positively associated with job embeddedness directly and indirectly through the parallel mediating roles of work–family conflict and enrichment. Emphasis should be placed on the dimensions of social support and skill diversity within job resources, as these aspects are more likely to enhance nurses’ job embeddedness.